2012
DOI: 10.1021/ie301751y
|View full text |Cite
|
Sign up to set email alerts
|

Rolling Ball Viscometer Calibration with Gas Over Whole Interest Range of Pressure and Temperature Improves Accuracy of Gas Viscosity Measurement

Abstract: A practical method for measuring gas viscosity uses gas to calibrate the rolling ball viscometer over the whole interest range of pressure and temperature. It reduces the turbulent effect of gas flow around the ball. The viscometer calibration at only atmospheric pressure yields poor results, because it cannot accommodate the turbulent effect at higher pressures. We used nitrogen to calibrate the viscometer for the pressure up to 8,000 psia and temperature up to 260 °F. Optimal tube inclination angle and also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…53 by the new correlation. Lines are drawn to help the reader to discern the variations of the deviations with pressure and temperature.…”
Section: Figmentioning
confidence: 96%
See 4 more Smart Citations
“…53 by the new correlation. Lines are drawn to help the reader to discern the variations of the deviations with pressure and temperature.…”
Section: Figmentioning
confidence: 96%
“…However, the data were neither reported in the publication nor were they provided upon request of the present authors. Davani et al 53 reported measurements with a rolling-sphere viscometer at nine temperatures from 309.82 K to 388.71 K and at five pressures from 27.6 MPa to 55.2 MPa. Vogel 23 recalculated the results of Vogel and Barkow of 1986 54 and those of Hendl et al of 1993 55 by referencing them to the highly accurate viscosity value of helium at room temperature by Cencek et al 28 Locke et al 56 contributed five data points for gaseous CO 2 at 303.2 K and pressures from 0.5 MPa to 4.5 MPa that were measured with a newly developed vibrating-wire viscometer.…”
Section: Review Of Viscosity Datamentioning
confidence: 99%
See 3 more Smart Citations